1999
DOI: 10.1074/jbc.274.33.23316
|View full text |Cite
|
Sign up to set email alerts
|

Docking of Linear Peptide Antagonists into the Human V1a Vasopressin Receptor

Abstract: Phpa-LVA (covalent attachment to transmembrane domain VII), threedimensional models of the antagonist-bound receptors were constructed and then verified by site-directed mutagenesis studies. Strikingly, these two linear peptide antagonists, when bound to the V 1a receptor, could adopt a pseudocyclic conformation similar to that of the cyclic agonists. Despite divergent functional properties, these peptide antagonists could interact with a transmembrane-binding site significantly overlapping that of the natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
71
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 42 publications
(81 reference statements)
6
71
0
Order By: Relevance
“…This model has been extensively tested by means of site-directed mutagenesis (Mouillac et al 1995) and successfully used to identify the receptor residues responsible for selective agonist binding affinity (Chini et al 1995) and efficacy (Chini et al 1996). It has also been recently exploited to explain the pharmacological behaviour of the vasopressin 2 (V,) receptor mutants responsible for clinical forms of congenital nephrogenic diabetes insipidus (Ala et al Albertazzi et al 2000), and to identify the putative docking site for peptidergic linear antagonists in the VIa receptor subtype (Phalipou et al 1999). …”
Section: Oxytocin and Vasopressin Receptor Binding Sitesmentioning
confidence: 99%
“…This model has been extensively tested by means of site-directed mutagenesis (Mouillac et al 1995) and successfully used to identify the receptor residues responsible for selective agonist binding affinity (Chini et al 1995) and efficacy (Chini et al 1996). It has also been recently exploited to explain the pharmacological behaviour of the vasopressin 2 (V,) receptor mutants responsible for clinical forms of congenital nephrogenic diabetes insipidus (Ala et al Albertazzi et al 2000), and to identify the putative docking site for peptidergic linear antagonists in the VIa receptor subtype (Phalipou et al 1999). …”
Section: Oxytocin and Vasopressin Receptor Binding Sitesmentioning
confidence: 99%
“…1) in the human V 1a receptor, we used 3D models of the rat and human AVP receptors [4,16,17,21]. These models suggest that hydrophobic residues potentially involved in the ligand binding are aromatic and localized at the bottom of the receptor binding pocket.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Studies of chimeric OT/V 2 receptors have shown that TM VII contributes to the binding of an OT antagonist [15]. To identify the receptor domains that contribute to the binding of V 1a antagonists, we developed two radioiodinated photosensitive ligands used to covalently label the human V 1a receptor [16,17]. Combining photoaffinity labeling and receptor fragmentation, we clearly demonstrated that covalent attachment of the antagonists occurs in TM VII and in the first extracellular loop of the receptor, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations